TRAIL-induced apoptosis requires Bax-dependent mitochondrial release of Smac/DIABLO - Deng, Yibin (Cold Spring Harbor Laboratory Press, 2002)
Recent reports suggest that a cross-talk exists between apoptosis pathways mediated by mitochondria and cell death receptors. In the present study, we report that mitochondrial events are required for apoptosis induced by the cell death ligand TRAIL (TNF-related apoptosis-inducing ligand) in human cancer cells. We show that the Bax null cancer cells are resistant to TRAIL-induced apoptosis. Bax deficiency has no effect on TRAIL-induced caspase-8 activation and subsequent cleavage of Bid; however, it results in an incomplete caspase-3 processing because of inhibition by XIAP. Release of Smac/DIABLO from mitochondria through the TRAIL–caspase-8–tBid–Bax cascade is required to remove the inhibitory effect of XIAP and allow apoptosis to proceed. Inhibition of caspase-9 activity has no effect on TRAIL-induced caspase-3 activation and cell death, whereas expression of the active form of Smac/DIABLO in the cytosol is sufficient to reconstitute TRAIL sensitivity in Bax-deficient cells. Our results show for the first time that Bax-dependent release of Smac/DIABLO, not cytochrome c, from mitochondria mediates the contribution of the mitochondrial pathway to death receptor-mediated apoptosis.